Faktor yang berhubungan dengan kepatuhan berobat penderita tuberkulosis paru di kota Sorong - Meliana Depo; Dirgantari Pademme (Jurnal Teknosains, 2022)
Tuberculosis is still a major burden of disease in Indonesia. The disease is highly transmissible, and if it is resistant to drugs, treatment can be take a long time. Patients with pulmonary tuberculosis will be difficult to cure if there is no regular treatment. This study aims to identify factors related to patient adherence to tuberculosis treatment in Sorong City. The study uses a cross-sectional design with 72 respondents. Data collection through interviews with a structured questionnaire. Samples were pulmonary tuberculosis patients recorded as having followed treatment for at least two months from 2018 to 2019 at RSUD Sorong. Data were analysed using the Chi-square test. The results showed that 55.6% of respondents adhered to treatment for pulmonary tuberculosis. The variables associated with adherence in patients with pulmonary tuberculosis in Sorong City were drug side effects (p-value = 0.013) and the support of the supervisor taking medication (p-value = 0.000). In order to improve adherence to tuberculosis treatment, health workers should create a tracking system for patients who are non-compliant and expand case management’s capacity to advise patients.